Youth Mentoring as a Viable Crime Prevention Strategy: Evidence and Ontario Policy, with Reflections from Some Mentors - Bradley, Jeffrey (Université d'Ottawa / University of Ottawa, 2018)
This thesis explored whether youth mentoring could be used as a crime prevention strategy for Ontario. It examined risk factors for youth crime and social bonding theory, the effectiveness of selected programs to prevent crime and best practices, and Ontario government reports on effective crime prevention. It also explored youth mentoring in practice with some mentors from Big Brothers Big Sisters of Ottawa and Sudbury Ontario. The analysis of the literature on risk factors for youth crime identified a number of individual, relationship, community, and societal level factors that correlate with the likelihood of a young person engaging in crime. Travis Hirschi’s social bonding theory provided a lens to understand the contribution mentoring can have on preventing crime through attachment, commitment, involvement, and belief with parents and schools. The evidence-based research on the effectiveness of selected programs that had a mentoring component showed that the likelihood of offending could be reduced with other well-being indicators. Research on mentoring relationships showed that when mentors focused on the assets of the youth and were committed to the relationship, they could foster a lasting emotional bond. Best practices of an effective youth mentoring program included outreaching to vulnerable youth, involving parents, screening and training mentors, matching mentors and mentees based on background, having mentoring connected to a larger strategy, following a developmental approach, and developing standards for implementation. The recent reports from the Province of Ontario on crime prevention and community safety use much of the same evidence on risk factors and social development programs to confirm that prevention is an effective way to reduce crime. These reports also point to strong public support for government investment in prevention and education over punishment. The semi-structured interviews with mentoring practitioners in Sudbury and Ottawa, Ontario analyzed the methods used by mentors volunteering with high-risk youth in the Big Brothers Big Sisters community-based program. Results showed the organizational procedure, youth and risk factors, the bonding process between mentors and mentees, and challenges of mentoring at-risk youth were important. Mentors had positive beliefs on the impacts mentoring had on preventing crime and violence. Therefore, youth mentoring is a crime prevention strategy consistent with evidence and government reports and so is viable, but will require political support and investment upstream to make a difference across the province.
Keywords: Crime Prevention; Social Development; Social Bonding; Youth Mentoring